Primera identificación de Echinococcus vogeli en una paca en la provincia de Misiones, Argentina - Vizcaychipi, Katherina A. (2013)
Abstract We report the fi rst fi nding of Echinococcus vogeli in a paca, Cuniculus paca, in the tropical forest of Misiones, in the north of Argentina. The presence of the bush dog, Speothos venaticus, E. vogeli´s only natural defi nitive host, was also reported. The polycystic hydatids, 2 to 3 cm in diameter, were only found in the liver of an adult paca. The size range of the hooks and the relative proportion blade/handle did not show signifi cant differences with respect to the ones reported for E. vogeli. The size of E. granulosus hooks, measured for comparison purposes, was signifi cantly smaller (p < 0.0001). These results confi rmed the presence of E. vogeli in Argentina. The probability of fi nding neotropical echinococcosis in humans reinforces the need to expand the search for E. vogeli in Argentina. Echinococcosis due to E. vogeli is very aggressive and may cause death in about a third of the human population affected